IMPLEMENTASI LARANGAN MEROKOK DI JALAN SEBAGAI UPAYA KESELAMATAN BERKENDARA DALAM PERSPEKTIF HUKUM TRANSPORTASI - NIM. A1012211146, ABDUL KHAIR IMADUDDIN (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract Road safety is a crucial aspect of transportation law aimed at protecting the rights and safety of road users. One factor that can disrupt a driver's concentration is the habit of smoking while driving, which can increase the risk of accidents. This study examines the implementation of the smoking ban on the road based on Article 106 Paragraph (1) of Law Number 22 of 2009 concerning Road Traffic and Transportation (UU LLAJ) and Minister of Transportation Regulation Number 12 of 2019 (Permenhub No. 12/2019). Both regulations emphasize the obligation for drivers to drive with full concentration and prohibit activities that may distract attention, including smoking. The findings reveal that the implementation of this ban has not been effective due to several obstacles. First, incomplete regulations